'Two's company, three's a crowd'. (31st August 2021) - Houen, Sandy; Danby, Susan
Abstract : This paper examines how young children mobilize interactional resources to position peers as neither fully included nor fully excluded in a preschool classroom. A single case of a video recording of three preschool-aged girls was analysed using conversation analysis. Two girls restricted access to a third girl and positioned her on the periphery in peer activity. The third girl's entry into the activity was restricted through the other two's claims of object ownership, limited physical access to objects, multi-modal practices that diverted attention away from the coveted objects, and assessments and sanctions around engagement with an object. The recurrent attempts to keep out the third girl were undertaken through partitioning. Findings highlight how children protect dyadic relationships.